2002
DOI: 10.1007/s00122-001-0825-9
|View full text |Cite
|
Sign up to set email alerts
|

Bay-0 × Shahdara recombinant inbred line population: a powerful tool for the genetic dissection of complex traits in Arabidopsis

Abstract: Natural genetic variation in Arabidopsis is considerable, but has not yet been used extensively as a source of variants to identify new genes of interest. From the cross between two genetically distant ecotypes, Bay-0 and Shahdara, we generated a Recombinant Inbred Line (RIL) population dedicated to Quantitative Trait Locus (QTL) mapping. A set of 38 physically anchored microsatellite markers was created to construct a robust genetic map from the 420 F6 lines. These markers, evenly distributed throughout the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
369
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(400 citation statements)
references
References 50 publications
(58 reference statements)
29
369
2
Order By: Relevance
“…The locus on which we have focused explains a large proportion of variation in the focal plant traits (an average of 12% of the variance per trait, with a maximum of 20% in silique number; table 1). This locus was previously identified by Loudet et al [34] in a study of flowering time and maps to a region of the genome that encompasses the FRI gene. FRI has previously been shown to have pleiotropic effects on fitness-related traits [42,43], and our analysis shows that it appears to also have relatively strong indirect effects on partners (the indirect effects alone are significant at the genome level).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The locus on which we have focused explains a large proportion of variation in the focal plant traits (an average of 12% of the variance per trait, with a maximum of 20% in silique number; table 1). This locus was previously identified by Loudet et al [34] in a study of flowering time and maps to a region of the genome that encompasses the FRI gene. FRI has previously been shown to have pleiotropic effects on fitness-related traits [42,43], and our analysis shows that it appears to also have relatively strong indirect effects on partners (the indirect effects alone are significant at the genome level).…”
Section: Discussionmentioning
confidence: 94%
“…Genotypes were assigned the index values of þ1 and 21 for the Bay-0 and Shahdara homozygotes at a locus, respectively, Therefore positive allelic effects can be interpreted as the effect of replacing the Shahdara allele with the Bay-0 allele [34]. Because of deviations from normality, we natural log-transformed BOLT and square root-transformed WT, BUD, FLWR, SILIQ and BRANCH for both the focal and partner traits.…”
Section: Materials and Methods (A) Experimental Designmentioning
confidence: 99%
“…Sequencing studies have demonstrated the existence of hundreds of SNPs between accessions Bayreuth (Bay-0) and Shahdara (Sha), but these polymorphisms had not been developed into tractable genetic markers (Nordborg et al 2005). To add markers to the existing genotypic data for the Bay-0 ‫ן‬ Sha RIL population (Loudet et al 2002), we used gene expression microarray data that had been generated as part of a larger experiment to measure transcriptional variation in these RILs to assess genotypes and produce detailed haplotypes. The SFP markers and GEMs we identified were used to construct a detailed genetic linkage map that was consistent with the gene order predicted by the genomic sequence of the Col-0 accession (The Arabidopsis Genome Initiative 2000) with minimal missing data.…”
mentioning
confidence: 99%
“…Nevertheless, the resulting maps were still at relatively low resolution (Eshed and Zamir 1995;Loudet et al 2002;Simon et al 2008). Recently, the emergence of next-generation sequencing technology greatly augmented the sequencing throughputs and reduced both time and cost simultaneously, and might make population-scale QTL studies feasible (Charlesworth and Willis 2009).…”
Section: Discussionmentioning
confidence: 99%